2020
DOI: 10.2147/dddt.s235491
|View full text |Cite
|
Sign up to set email alerts
|

<p>Panax Notoginseng Ameliorates Podocyte EMT by Targeting the Wnt/β-Catenin Signaling Pathway in STZ-Induced Diabetic Rats</p>

Abstract: Introduction: Epithelial-mesenchymal transition (EMT) may contribute to podocyte dysfunction in diabetic nephropathy (DN). Aiming to identify novel therapeutic options, we investigated the protective effects of Panax notoginseng (PN) on podocyte EMT in diabetic rats and explored its mechanisms. Methods: Diabetes was induced in rats with streptozotocin (STZ) by intraperitoneal injection at 55 mg/kg. Diabetic rats were randomly divided into three groups, namely, diabetic rats, diabetic rats treated with berapros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Healthy 8-week-old male Sprague-Dawley rats weighing 200–250 g were housed under a constant 12 h light–dark cycle at a temperature between 21 and 23°C and allowed free access to food and water. Diabetes was induced in rats by a single intraperitoneal injection of STZ at 55 mg/kg, according to our previous study ( Xie et al, 2020 ). Seventy-two hours after intraperitoneal injection of STZ, the blood glucose level was measured from the tail vein, and rats with a blood glucose level above 16.7 mmol/L were considered as diabetic rats ( Xie et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy 8-week-old male Sprague-Dawley rats weighing 200–250 g were housed under a constant 12 h light–dark cycle at a temperature between 21 and 23°C and allowed free access to food and water. Diabetes was induced in rats by a single intraperitoneal injection of STZ at 55 mg/kg, according to our previous study ( Xie et al, 2020 ). Seventy-two hours after intraperitoneal injection of STZ, the blood glucose level was measured from the tail vein, and rats with a blood glucose level above 16.7 mmol/L were considered as diabetic rats ( Xie et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes was induced in rats by a single intraperitoneal injection of STZ at 55 mg/kg, according to our previous study ( Xie et al, 2020 ). Seventy-two hours after intraperitoneal injection of STZ, the blood glucose level was measured from the tail vein, and rats with a blood glucose level above 16.7 mmol/L were considered as diabetic rats ( Xie et al, 2020 ). The diabetic rats were then randomly divided into four groups ( n = 7/each group): 1) STZ-induced diabetic rats (STZ), received an equal volume of olive oil; 2) diabetic rats treated with losartan at 10 mg·kg −1 ·d −1 ; 3) diabetic rats treated with low-concentration of AS II at 3.2 mg·kg −1 ·d −1 (ASIIL); 4) diabetic treated with high-concentration of AS II at 6.4 mg·kg −1 ·d −1 (ASIIH).…”
Section: Methodsmentioning
confidence: 99%
“…With this purpose, potential interactions with USP36 were speculated in string 1 (Figure 4A). Among these proteins, particularly interest is DOCK4, due to its function in activating Wnt/βcatenin signaling pathway, which is associated with renal fibrosis (Xie et al, 2020). First, we evidenced that USP36 physically interacts with DOCK4 by IP and in situ proximity ligation assay (in situ PLA) ( Figures 4B,C).…”
Section: Usp36 Regulates the Ubiquitination Level Of Dock4mentioning
confidence: 85%
“…Previous studies demonstrated that DOCK4 is responsible for the degradation of β-catenin (Xie et al, 2020). Under this study, whether USP36 has an effect on EMT through DOCK4-dependent Wnt/β-catenin signaling pathway in TECs under high glucose condition has aroused our attention.…”
Section: Usp36 Regulates Emt Of Tecs Via Dock4-dependent Wnt/β-catenin Signaling Pathwaymentioning
confidence: 90%
“…Panax notoginseng (PN) targets the Wnt/β-catenin signaling pathway in rats. By increasing the expression of Wnt1, β-catenin, and Snail, PN can upregulate the expression of desmin and α-SMA protein and reduce the expression of nephrin, thereby ameliorating podocyte EMT [70]. Emodin is extracted from Polygonum cuspidatum, rhubarb, and other rhizomes from a class of bioactive substances which possess anti-inflammatory, antioxidative, and other pharmacological activities.…”
Section: Wnt Signalingmentioning
confidence: 99%